In situ biosynthesis of bacterial nanocellulose-CaCO3 hybrid bionanocomposite: one-step process - Mohammadkazemi, Faranak (2016)
In this work, a simple and green route to the synthesis of the bacterial nanocellulose-calcium carbonate (BNC/CaCO3) hybrid bionanocomposites using one-step in situ biosynthesis was studied. The CaCO3 was incorporated in the bacterial nanocellulose structure during the cellulose biosynthesis by Gluconacetobacter xylinus PTCC 1734 bacteria. Hestrin-Schramm (HS) and Zhou (Z) culture media were used to the hybrid bionanocomposites production and the effect of ethanol addition was investigated. Attenuated total reflection Fourier transform infrared spectroscopy, field emission scanning electron microscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy, inverse gas chromatography and thermogravimetric analysis were used to characterize the samples. The experimental results demonstrated that the ethanol and culture medium play an important role in the BNC/CaCO3 hybrid bionanocomposites production, structure and properties. The BNC/CaCO3 biosynthesized in Z culture medium revealed higher O/C ratio and amphoteric surface character, which justify the highest CaCO3 content incorporation. The CaCO3 was incorporated into the cellulosic matrix decreasing the bacterial nanocellulose crystallinity. This work reveals the high potential of in situ biosynthesis of BNC/CaCO3 hybrid bionanocomposites and opens a new way to the high value-added applications of bacterial nanocellulose.